Diurnal and seasonal variability in size-dependent atmospheric deposition fluxes of polycyclic aromatic hydrocarbons in an urban center - Kai Zhang; Zhang, Bao-Zhong; Li, Shao-Meng; Zhang, Lei-Ming; Staebler, Ralf; Zeng, Eddy Y. (ATMOSPHERIC ENVIRONMENT, 2012)
Atmospheric gaseous and size-segregated particle samples were collected from urban Guangzhou at the heights of 100 and 150 m above the ground in daytime and at night in August and December 2010, and were analyzed for polycyclic aromatic hydrocarbons (PAHs). Particulate PAHs were more abundant at night than in daytime, and significantly higher in winter than in summer. The observed vertical, diurnal, and seasonal variability in the occurrences of PAH were attributed to varying meteorological conditions and atmospheric boundary layers. More than 60% of the particulate PAHs were contained in particles in the accumulation mode with an aerodynamic diameter (D-p) in the range of 0.1-1.8 mu m. Different mass transfer velocities by volatilization and condensation are considered the main causes for the different particle size distributions among individual PAHs, while combustion at different temperatures and atmospheric transport were probable causes of the observed seasonal variation in the size distribution of PAHs. Based on the modeled size-dependent dry deposition velocities, daily mean dry deposition fluxes of particulate PAHs ranged from 604 to 1190 ng m(-2) d(-1), with PAHs in coarse particles (D-p > 1.8 mu m) accounting for 55-95% of the total fluxes. In addition, gaseous PAHs were estimated to contribute 0.6-3.1% to the total dry deposition fluxes if a conservative dry deposition velocity for gaseous species (2 x 10(-4) m s(-1)) were used. Finally, disequilibrium phase partitioning, meteorological conditions and atmospheric transport were regarded as the main reasons for the variances in dry deposition velocities of individual PAHs. (C) 2012 Elsevier Ltd. All rights reserved.